Analysis of the Adaptability of Nurses during the Covid-19 Pandemic - Ainul Mufarichah; Pardiman Pardiman; Siti Asiyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Health workers in Indonesia who carry out medical service duties at the forefront during the COVID-19 pandemic have twice the risk of experiencing burnout syndrome. Furthermore, doctors who treat COVID-19 patients, both general practitioners and specialists, are twice as likely to experience emotional exhaustion and loss of empathy as those who do not treat COVID-19 patients. This study aims to examine the effect of the pandemic situation on adaptive performance and burnout syndrome. Furthermore, to determine the moderating role of management support between the influence of the pandemic situation on adaptive performance and burnout syndrome on adaptive performance. The data was obtained by purposive sampling on nurses working in the COVID-19 pandemic situation at Prasetya Husada Hospital in Malang Regency as many as 84 people out of 104 total population. Hypothesis testing using Warpps 7.0 path analysis. The results showed that there was a positive and significant effect of the COVID-19 pandemic situation on burnout syndrome. There was a positive and significant effect of the COVID-19 pandemic situation on adaptive performance. There is a positive and significant effect of burnout syndrome on adaptive performance. There is a significant influence from the COVID-19 pandemic situation which is moderated by the perception of management support (moderation 1) on adaptive performance. There is a significant effect of burnout syndrome moderated by perceived management support (moderation 2) on adaptive performance.